2021
DOI: 10.3390/ijerph182111022
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Perspectives on Restraint Use in Aged Care

Abstract: Restraint use in Australian residential aged care has been highlighted by the media, and investigated by researchers, government and advocacy bodies. In 2018, the Royal Commission into Aged Care selected ‘Restraint’ as a key focus of inquiry. Subsequently, Federal legislation was passed to ensure restraint is only used in residential aged care services as the ‘last resort’. To inform and develop Government educational resources, we conducted qualitative research to gain greater understanding of the experiences… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The following reasons were given for restraining the patients: age, care dependency, level of disablement, impaired activities of daily living, cognitive status, dementia, Alzheimer's, Parkinson's, negative mood, hallucinations, delusions, disorientation/confusion, depression, preventing dislodgement of feeding tubes, safe use of medical devices, workload, staff culture, location and availability of human resources, negative experiences of nurses, concerns and uncertainties of relatives and legal guardians, and organizational problems such as staff fluctuations and shortages of physicians. The largest number of studies (13) reported the prevention and/or risk of falls to be the main reason for using physical restraints, followed by behavioral problems such as wandering (7), verbal or physical agitation (6), being verbally or physically abusive (1), injury to others (1), shouting, restlessness, aggressiveness, disrobing in public, and resisting care (1), functional impairment (1), urinary or fecal incontinence (3), hip fracture/fall-related fractures (2), history of falls (1), bedfast (1), and being untidy (1). The risk of self-injury was reported in three studies (Finland, Israel, and Singapore) as being the reason for using restraints.…”
Section: Reasons For Physical Restraint Usementioning
confidence: 99%
“…The following reasons were given for restraining the patients: age, care dependency, level of disablement, impaired activities of daily living, cognitive status, dementia, Alzheimer's, Parkinson's, negative mood, hallucinations, delusions, disorientation/confusion, depression, preventing dislodgement of feeding tubes, safe use of medical devices, workload, staff culture, location and availability of human resources, negative experiences of nurses, concerns and uncertainties of relatives and legal guardians, and organizational problems such as staff fluctuations and shortages of physicians. The largest number of studies (13) reported the prevention and/or risk of falls to be the main reason for using physical restraints, followed by behavioral problems such as wandering (7), verbal or physical agitation (6), being verbally or physically abusive (1), injury to others (1), shouting, restlessness, aggressiveness, disrobing in public, and resisting care (1), functional impairment (1), urinary or fecal incontinence (3), hip fracture/fall-related fractures (2), history of falls (1), bedfast (1), and being untidy (1). The risk of self-injury was reported in three studies (Finland, Israel, and Singapore) as being the reason for using restraints.…”
Section: Reasons For Physical Restraint Usementioning
confidence: 99%
“…RP are typically broken down into categories such as physical, chemical, mechanical, environmental, seclusion, psychosocial or psychological [ 8 , 9 ]. Research on RP use is complicated by the lack of a common definition for the individual categories of RP and their measurement [ 10 12 ].…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Among older adults, physical restraint use is associated with negative psychological and physical effects, such as depression, anxiety, delirium, post‐traumatic stress, loss of strength, bone and muscle mass, incontinence, pneumonia 2,3 and increased functional and cognitive decline 4 . Restraint use has been widely studied in nursing homes where many countries prohibit use, 2,4,5 however, less is understood about restraint use at home 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…4 Restraint use has been widely studied in nursing homes where many countries prohibit use, 2,4,5 however, less is understood about restraint use at home. 6,7 A recent systematic review found only four studies (all conducted in Europe) estimating a prevalence of restraint use in home care of older adults generally, ranging between five and 25%, 8 with varying understandings of what constituted restraint. 9 Another study in Japan found that 40.5% of home care providers had observed physical restraints.…”
Section: Introductionmentioning
confidence: 99%